A little note to God: A struggle against malignant cancer - Wajdi, Majid; Abdurrahim, Abdurrahim; Wagisuari, Ni Kadek Nara; Narayasa, Ni Made Irene Kharisma; Ningtyas, Diyah Ayu; Pratiwi, Ni Luh Putu Dina (Journal of Language and Pragmatics Studies, 2023)
Surat Kecil Untuk Tuhan (A note for God) is a book based on the true story of the struggle of an Indonesian teenage girl named Gitta Sesa Wanda Cantika or Keke against malignant cancer. Keke, who is only 13 years old, is a beautiful, smart girl and a former child singer who was suddenly diagnosed with a rare disease called rhabdomyosarcoma which is a kind of cancer that changes her face just that makes  anyone have difficulty recognizing her. Cancer attacked her face and made her beautiful face look like a monster, the doctor said that she only had a few months to live. Hearing the verdict, Keke's father did not give up, he fought so that Keke could escape the death sentence. The father's struggle to save his daughter was so moving, Keke, who realized that her life would end, then wrote a small letter to God. God gave a gift in her life, and Keke was able to survive cancer for three years even though she finally gave up. This report was made with the aim of seeing how someone who is affected by a rare disease struggles and never gives up against cancer.